The Religious Dimension in Human Urbanization According to Ibn Khaldun Through his Book Introduction - Fathi Jawhar Farmazi. (Zanco Journal of Humanity Sciences)
This research is devoted to the hadith pioneer and founder of the science of urbanism, and on the religious dimension in the thought of Ibn Khaldun, and the role of religion in human urbanization when he spoke about the emergence and development of the history of nations and peoples, in his book Introduction. Ibn Khaldun spoke about the human being as the primary engine of urbanization, and he also spoke about religion on the basis that he was educated in a religious way, and that the sciences he studied did not come out of the religious framework, such as jurisprudence, law and history. Because of the nature of this scientific upbringing and the firmness of these sciences in his convictions, and his firm belief in the vital role of religion in the life of the individual and society, he considered religion the correct and most important means to which a person uses in achieving urbanization, and that there is no existence of the emergence of construction except through religion and work in the light of its principles. He tries to prove that the reason for the progress of peoples is to resort to a combination of the religious and the worldly, and that the world is a mount for the afterlife. And that the delay and demise of urbanization, but the reason for it is the distance from religion. In order to find out his views and theory in this area, we have divided this research into three sections. In the first topic we talked about Ibn Khaldun and his introduction to history and his role in human development. In the second topic, we dealt with the search for religion and man in the thought of Ibn Khaldun and the opinions of scholars regarding his religious inclinations. In the third topic, we shed light on the religious dimension in human urbanization according to Ibn Khaldun.